Professional Services Training to Enhance Job Readiness of Vocational Students at SMKN 8 North Bengkulu - Suwarni, Suwarni; Soleh , Ahmad; Wagini, Wagini; Panjaitan , David; Gustika , Soni; Gandi , Ramanda (Universitas Dehasen Bengkulu, 2025)
This community service program was conducted by lecturers from Universitas Dehasen Bengkulu to enhance the job readiness of students at SMKN 8 North Bengkulu through professional services training. The program focused on developing service excellence, effective communication, customer handling, professional behavior, and work ethics. The training was implemented using a workshop approach that combined theoretical explanations, practical demonstrations, role-playing, and direct practice to simulate real service situations.The results of the training indicate that students of SMKN 8 North Bengkulu showed significant improvements in confidence, communication skills, service behavior, and understanding of workplace expectations. Participants were able to apply service standards more effectively during simulation activities, and teachers observed positive changes in students’ attitude and readiness for employment.This program demonstrates that structured, practice-oriented professional services training can effectively prepare vocational students for service-oriented industries, enhance their soft skills, and increase their competitiveness in the workforce.